Application of Membrane Bioreactor (MBR) for Antibiotic Elimination From Wastewater - Van Son, Tran; Tuyet Mai, Vu Thi (VNU Journal of Science: Earth and Environmental Sciences, 2024)
In this study, a membrane bioreactor – MBR system at laboratory-scale was designed to remove sulfamethoxazole (SMX) in water. The system consists of a 8-liter aerobic tank combined with a hollow fiber micro filtration membrane (MF). Influent flow rate of wastewater was 15,84 L/day. Affecting factors to treatment efficiencies (organic pollutants and antibiotics) such as contact time and initial antibiotic concentration were investigated. Experimental results indicated that wastewater with initial parameters COD, NH 4 + , NO 3 - , PO 4 3- were respectively 240, 9,4, 37,5, 6,3 mg/L, the treatment efficiencies achieved were respectively at 63,4, 89,7, 78,1, and 79,8%. The removal efficiencies of the wastewater containing SMX (concentrations range from 0,052 to 0,268 mg/L) for COD and NH 4 + decreased by 4,2 and10,9% respectively, and for NO 3 - and PO 4 3- increased by about 4,5 and 7,9%, correspondingly. Overall SMX elimination performance is about 49,7%.